Epithelioid Haemangioendothelioma of the mandibular gingiva: case report and literature review. (2015) - Ali, Shabnum; Odell, E.W.; Whaites, E.; Robinson, P.D.; Challacombe, S.J.
Highlights: This paper demonstrates that oral EHE is an unpredictable lesion that seems to behave in a relatively benign fashion. This is in contrast with non-oral EHE where up to one third of cases may metastasize. Because of the propensity to recur locally after excision and curettage, a wide local excision with close clinical follow has been suggested in the literature as the treatment of choice for oral lesions. However, the lack of metastases from oral lesions, the small size, mandibular site and bland histology in this case suggests that a limited soft tissue excision and bone curettage, with long term follow-up would be appropriate for similar gingival lesions in future. Abstract: Introduction: Epithelioid hemangioendothelioma (EHE) is a rare vascular neoplasm that exhibits the potential for recurrence and metastasis but rarely involves the oral cavity. Presentation Of Case: We report the management and long term follow up of recurrent EHE in a 23- year-old woman. The lesion initially presented as a small area of erythematous gingival swelling with localised bone loss around the lower anterior teeth. It was treated by buccal and lingual stripping of the gingival tissues. The patient suffered local recurrence after 7 years and was treated with a wider surgical excision of the buccal and lingual gingivae, conserving the adjacent teeth and bone with an excellent cosmetic outcome. Over 21 years later, there have been no further recurrences. Discussion: This case highlights the management challenges of EHE and is the only case in the literature to have reported a case of mandibular gingivae with a long review period of 21 years. Conclusion: Oral EHE is an unpredictable lesion with a relatively benign course, unlike non-oral EHE where up to one third of cases may metastasise. Because of the propensity to recur locally after excision and curettage, a wide local excision with close clinical follow has been suggested in the literature as the treatment of choice for oral lesions. However, the lack of metastases from oral lesions, the small size, mandibular site and bland histology in this case suggests that a limited soft tissue excision and bone curettage, with long term follow-up would be appropriate for similar gingival lesions in future.